Reshaping the graduate education of scientists and engineers (National Academy Press, 1995)
Presents the electronic book "Reshaping the Graduate Education of Scientists and Engineers" by the National Academy of Sciences and published by National Academy Press. Notes that graduate work in science and engineering must coincide with modern industry standards and skills requirements.